Thermodynamic analysis of the solubility and preferential solvation of sulfamerazine in (acetonitrile + water) cosolvent mixtures at different temperatures (2019)
Solubility studies are valuable tools for the pharmaceutical industry and research centres and are currently becoming increasingly relevant in the environmental sciences field. This study presents the thermodynamic and preferential solvation analyses of solubility of sulfamerazine (SMR) in {acetonitrile (1) + water (2)} cosolvent mixtures at different temperatures (278.15–318.15 K). The maximum solubility of SMR was obtained at 318.15 K when mass fraction is w1 = 0.90, whereas the minimum solubility of SMR was obtained in pure water at 278.15 K. Based on the solubility data, the Gibbs and van't Hoff equations were used for obtaining the apparent thermodynamic dissolution functions, while the IKBI model was used for obtaining the preferential solvation coefficients. Thus, the dissolution process is endothermic and is heavily dependent on the polarity of the medium, favoring the entropy of thermodynamic solution functions in every case. With respect to the preferential solvation coefficients, the results indicate that SMR is preferentially hydrated in water- and acetonitrile-rich mixtures and that it is preferentially solvated by acetonitrile in mixtures having intermediate compositions (0.25 < x1 < 0.85). The Jouyban-Acree-van't Hoff model is applied for modeling the generated solubility data with reasonable accuracy.